Neuroticism and Religiosity: The Role of Obsessive Beliefs, Thought-Control Strategies and Guilt in Scrupulosity and Obsessive-Compulsive Symptoms Among Muslim Undergraduates - Inozu, Mujgan (Journal of religion and health, 2020)
Neuroticism and religiosity are distal vulnerability factors for OCD phenomenon. The present study aimed to examine the roles of obsessive beliefs (OBs), thought-control strategies, and guilt in the relationship between these vulnerability factors and obsessive-compulsive symptoms (OCSs), specifically scrupulosity symptoms in a Muslim sample via SEM. The sample consisted of 273 university students who filled out a set of questionnaires. The results indicated that neuroticism and the degree of religiosity predict OBs that are positively associated with guilt and self-punishment both of which predict scrupulosity and other OCSs. Findings of the present study were discussed in the context of the related literature.